Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3724/sp.j.1227.2012.00349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cloud, atmospheric water vapor, and dust on photosynthetically active radiation and total solar ra-diation in a Mongolian grassland

Abstract: Photosynthetically active radiation (PAR) is an important input parameter for estimating plant productivity due to its key role in the growth and development of plants. However, a worldwide routine network for systematic PAR measurements is not yet established, and PAR is often calculated as a constant fraction of total solar radiation (SR). Although the ratio of PAR to SR (PAR/SR) has been reported from many places, few studies have been performed for dry regions. The present study was therefore carried out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…That is, in cloudy and humid conditions, the absorption of solar radiation in the near infrared (NIR) portion of the solar spectrum is enhanced, whereas absorption in the PAR waveband does not vary significantly. Moreover, Bat-Oyun et al [59] equally observed that increases in PAR e /H were found under cloudy and humid conditions. The authors equally recorded a significant correlation between PAR e /H and water vapour pressure (r = 0.49, P < 0.001) for day time (08:00 -17:00, local time).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…That is, in cloudy and humid conditions, the absorption of solar radiation in the near infrared (NIR) portion of the solar spectrum is enhanced, whereas absorption in the PAR waveband does not vary significantly. Moreover, Bat-Oyun et al [59] equally observed that increases in PAR e /H were found under cloudy and humid conditions. The authors equally recorded a significant correlation between PAR e /H and water vapour pressure (r = 0.49, P < 0.001) for day time (08:00 -17:00, local time).…”
Section: Discussionmentioning
confidence: 94%
“…The influence of water vapour pressure on PAR/H has been roughly reported in literature in season variations such as the higher in summer (wet season) and lower in winter (dry season) [51,59,107]. This report is in agreement with recent report of dependence of PAR/H on water vapour pressure by Akitsu et al [49] who observed that the monthly mean PAR/H recorded higher values (0.465) in summer and lower value (0.420) in winter as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diurnal variation in PAR/H is variable between sites, e.g. with different degrees of midday depression (Alados et al 1996;Jacovides et al 2004;Udo and Aro 1999), midday increase (Ge et al 2011), slight increasing trend throughout the day (Aguiar et al 2012), as well as inconsistent diurnal changes from month to month (Bat-oyun et al 2012). The most commonly cited factor that explains the diurnal variation is water vapour.…”
Section: Monthly Average Of Daily Rainfall (Mm)mentioning
confidence: 99%
“…With the increasing use of spectrally selective devices, such as photovoltaic cells and coated glazings (Kanters et al, 2014;Wang et al, 2015), the scientific interest is not limited to the determining of the total or -broadband‖ solar irradiance reaching at the ground level, but now also encompasses its spectral distribution. This spectral distribution is also needed for industrial, biological, and medical applications such as evaluation of electrical energy, study of the photosynthetic activity of plants and evaluation of ultraviolet (UV) radiation (Bat-Oyun et al, 2012;Petkov et al, 2012;Bilbao et al, 2015). The scattering by air molecules and aerosols attenuates the solar radiation over its whole spectrum, while the absorption modifies it in selective spectral bands due to the action of various atmospheric constituents, mainly including ozone, water vapor, oxygen, carbon dioxide, and nitrogen dioxide (Leckner, 1978;Jacovides et al, 2005;Kanniah et al, 2010).…”
Section: Introductionmentioning
confidence: 99%